Jonas Pašakauskis (Jan Poszakowski). Compendium vitae of Father Mathias Casimirus Sarbiewski (prepared and translated from Latin by Ona Dilytė - Čiurinskienė) - Dilytė - Čiurinskienė, Ona (Senoji Lietuvos literatūra, 2024)
-
Keywords: -